Expanding Stakeholder Base: A Model for Social Value Creation through Collaboration in Workforce Literacy Development - Priya Darshini Kurup; Merlissa C. Alfred (Adult Education Research Conference, 2010)
Here, we present a conceptual model for a holistic approach to workforce literacy development. In this model we argue that the adult literacy development process is influenced by multiple stakeholders – literacy providers, government agencies, businesses, and communities. Interaction and interdependence between stakeholders results in emergence of the four Es of social value creation: Expertise development, Economic development, Engagement and Empowerment.